A critical evaluation of planktonic foraminiferal biostratigraphy across the Coniacian-Santonian boundary interval in Spain, Texas, and Tanzania - PETRIZZO M. R. (SEPM Special Publication, 2019)
Identification of the best sequence of planktonic foraminiferal events that is 12 reproducible across the Coniacian-Santonian boundary interval is determined by 13 comparison of data from three reference sections: the Cantera de Margas section at 14 Olazagutia in northern Spain (Global Boundary Stratotype Section and Point for the 15 base of the Santonian Stage), the Ten Mile Creek section in southern Texas (candidate 16 GSSP stratotype for the base of the Santonian Stage), and Tanzania Drilling Project 17 (TDP) Site 39 drilled in Tanzania. In the stratotype section the GSSP is marked by the 18 lowest occurrence of the inoceramid Cladoceramus undulatoplicatus (= Platyceramus 19 undulatoplicatus), which is comprised within the planktonic foraminiferal Dicarinella 20 asymetrica Zone, exhibits secondary microfossil events and a negative 0.3‰ excursion in δ13 21 C. The same bio- and chemostratigraphic records have been identified 22 in the Ten Mile Creek section in Texas. In Tanzania, Globotruncana linneiana, a 23 GSSP secondary planktonic foraminiferal marker event, has been used in the absence 24 of C. undulatoplicatus and of correlative chemostratigraphic tie-points. Planktonic foraminiferal composition in the three stratigraphic sections is similar 26 although discrepancies are observed in the reproducibility of some bioevents. 27 Similarities between sections include the same order of appearances of the index 28 species Sigalia carpatica, Costellagerina pilula and G. linneiana in the Cantera de 29 Margas section and TDP Site 39, and the absence of the single keeled globotruncanids 30 (Globotruncanita stuartiformis, G. elevata) in the Cantera de Margas and Ten Mile 31 Creek sections. This apparent diachronism mostly pertain to the paleobiogeographic 32 distributions and ecological preferences of species that developed and diversified 33 under specific paleoenvironmental conditions. Overall, the study of the three sections 34 allows derivation of a more accurate and reproducible sequence of planktonic 35 ...